Parametric study of a proposed small hydropower project at Gurara-Nigeria. Issue 1 (1st January 2021) - Emetere, Moses E.; Bello, Oluwaseyi; Afolalu, S.A.; Mamudu, A.O.; Amusan, L.M.; Iroham, C.O.; Odun-Ayo, I.
Abstract: The energy crisis in developing is increasing by the day due to immigration and an increase in population. Hydroelectricity has been spotted to be the cheapest alternative energy option that can be financed by the government and private investors. In this research, a parametric investigation on the proposed small hydropower project was carried at Gurara, Nigeria. This project aims to incorporate a 4 MW hydropower plant within the waterfall neighborhood that already serves as a tourist center. The remote sensing dataset was used to map out the study location's elevation and determine the possibility of a sustainable reservoir based on the rainfall pattern in the geographical location. It was observed that an average rainfall of 400 mm at efficiency between 0.65 and 0.75 would enable optimal energy generation. Also, it was found out that the bank elevation of the water path is equally important as designing the head-section of the hydroelectricity dam. Hence, the study location has enormous potentials to serve energy demands in Nigeria.